Aging-related Resiliency Theory Development - Evelyn Feliciano; Alfredo Feliciano; Daisy Palompon; Amira Boshra (Belitung Nursing Journal, 2022)
As a dynamic developmental process, the older population further displays the capacity to resist change over time, improve resilience, and keep a basis for the continuity working and progress over positive management of detrimental consequences of life risks and difficulties. This study aims at developing a theory that endeavors to explore the process of developing aging-related resiliency in people’s later in life that can lead to a successful aging experience. In the development of a theory, this study utilized a deductive reasoning approach specifically, using the axiomatic approach. Aging-related Resiliency Theory was efficaciously developed by three propositions generated from four axioms that were derived after reviewing several sets of literature and studies. This developed theory implies that various deleterious events in life activate older persons to respond, adapt, and recover effectively. Acceptance emerges as they acknowledge the natural effects of aging while taking adaptive strategies and supportive resources to be resilient to one’s environment. In this sense, it impacts their optimistic outlook towards successful aging. Based on the extraction of axioms, such propositions denoted those older adults call to respond with their total capacity to accept, adapt, recover, and continuously resist deleterious life experiences while using enriched coping strategies and resources towards an optimistic outlook in achieving successful aging. Therefore, emphasizing to improve their capacity to respond to natural decline to essential processes could benefit them at promoting a healthier life span.